PENGARUH GAYA KEPEMIMPINAN TERHADAP KINERJA PEGAWAI DI KANTOR DINAS PERHUBUNGAN KOMUNIKASI DAN INFORMATIKA KABUPATEN SIDENRENG RAPPANG - Hardi Hardi (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2018)
Target of this research is to know how influence of leadership style to performance of officer in office On duty Communication of Sub-Province information and communications of Sidenreng Rappang and to know factor- factor influencing style leadership of Head On duty Communication to officer performance in office On duty Communication of Sub-Province information and communications of Sidenreng Rappang. Method Research which is used in this research is quantitative research method (tables of percentage). Technics of data collecting namely by alloting quesioner to responder amounting to 36 one who consist of public servant of Civil On duty Communication 16 people, staff of PHTL On duty Communication 20 people, and direct interview to informan amounting to 2 people. Of this research earn to explain that leadership style indicator to officer performance in office On duty Communication of and communications of informatika Sub-Province of Sidenreng Rappang covering to influence others 75 %, instructing behaviour 78,5%, reaching the target of organization 67,25%.Influence of Style Leadership to officer performance in Office On Duty Communication Of Communications And Information Sub-Province of Sidenreng Rappang there are factor - factor influencing that is ability 64,5%, motivation 64%, achievement 50% and environmental situation of [job/activity] 91,75. Indicator measurement of officer performance On duty existing Communication like, quality of human resource 68,75%, storey;level accuracy of time (officer discipline) 55,5%, and usage of technological resource 50,5%.